DEVELOPMENT OF COMPOSITIONS OF FILLED INSULATORS BASED ON SECONDARY RAW FOR MONOLITHIC HIGH-STRENGTH CONCRETE - A. Kh. Alaskhanov; T. S. Murtazaeva; M. S.-A. Saidumov; A. O. Omarov (Вестник Дагестанского государственного технического университета: Технические науки)
Objectives Development of compositions filled with binders based on recycled materials for monolithic high-strength concrete.Method The research methods adopted in the work are based on the theoretical principles and laws of designing and optimizing polydisperse multicomponent systems, the phase and structure formation of clinker minerals, the logic of mathematical calculations, the technological features of the structure formation of composite masses, the theoretical principles of controlling the rheological processes of mixes. All experimental data presented in the work were obtained according to the methods of current regulatory documents (GOST, recommendations, etc.).Result The paper provides an analysis of the experience of using recycled materials in the form of products of demolition of buildings and structures, the technology for producing secondary raw materials for concrete on their basis. Formulations filled with binders with an activity of 60-71 MPa with finely dispersed mineral fillers from concrete scrap and brick combat with a ratio of 70:30%, respectively, were developed and investigated.Conclusion The optimal formulations of highly mobile concrete mixtures were designed using local natural and technogenic raw materials with a grade of P5 cone sediment and persistence for more than 8 hours to obtain high-strength classes of compressive strength up to B60-B80 with unique operational properties.